Investigation of the inverse piezoelectric effect of trabecular bone on a micrometer length scale using synchrotron radiation. (1st October 2015) - Wieland, D.C.F.; Krywka, C.; Mick, E.; Willumeit-Römer, R.; Bader, R.; Kluess, D.
Graphical abstract: Abstract: In the present paper we have investigated the impact of electro stimulation on microstructural parameters of the major constituents of bone, hydroxyapatite and collagen. Therapeutic approaches exhibit an improved healing rate under electric fields. However, the underlying mechanism is not fully understood so far. In this context one possible effect which could be responsible is the inverse piezo electric effect at bone structures. Therefore, we have carried out scanning X-ray microdiffraction experiments, i.e. we recorded X-ray diffraction data with micrometer resolution using synchrotron radiation from trabecular bone samples in order to investigate how the bone matrix reacts to an applied electric field. Different samples were investigated, where the orientation of the collagen matrix differed with respect to the applied electric field. Our experiments aimed to determine whether the inverse piezo electric effect could have a significant impact on the improved bone regeneration owing to electrostimulative therapy. Our data suggest that strain is in fact induced in bone by the collagen matrix via the inverse piezo electric effect which occurs in the presence of an adequately oriented electric field. The magnitude of the underlying strain is in a range where bone cells are able to detect it. Statement of Significance: In our study we report on the piezoelectric effect in bone which was already discovered and explored on a macro scale in the 1950. Clinical approaches utilize successfully electro stimulation to enhance bone healing but the exact mechanisms taking place are still a matter of debate. We have measured the stress distribution with micron resolution in trabecular bone to determine the piezo electric induced stress. Our results show that the magnitude of the induced stress is big enough to be sensed by cells and therefore, could be a trigger for bone remodeling and growth.